Alternative zinc‐binding sites explain the redox sensitivity of zinc‐containing anti‐sigma factors. Issue 9 (17th June 2013) - Heo, Lim; Cho, Yoo‐Bok; Lee, Myeong Sup; Roe, Jung‐Hye; Seok, Chaok
ABSTRACT Certain bacterial zinc‐containing anti‐sigma (ZAS) factors respond sensitively to thiol‐induced oxidative stress by undergoing conformational changes, which in turn reduce binding affinities for their cognate sigma factors. This redox sensitivity provides a mechanism for coping with oxidative stress by activating the transcription of antioxidant genes. Not all ZAS proteins are redox‐sensitive, but the mechanism of redox sensitivity is not fully understood. Here we propose that alternative zinc‐binding sites determine redox sensitivity. To support this proposal, we performed protein modeling and zinc docking on redox‐sensitive and redox‐insensitive ZAS proteins complexed with their cognate sigma factors. At least one strong alternative zinc‐binding pocket was detected for all known redox‐sensitive ZAS factors in actinomycetes, while no strong alternative zinc‐binding pocket was identified in redox‐insensitive ZAS factors, except for one controversial case. This hypothesis of alternative zinc‐binding sites can also explain residue‐specific contributions to the redox sensitivity of RsrA, a redox‐sensing ZAS protein from Streptomyces coelicolor, for which alanine mutagenesis experiments are available. Our results suggest a mechanistic model for redox sensitivity as follows: zinc ion can probabilistically occupy multiple sites in redox‐sensitive ZAS proteins, increasing the susceptibility of zinc‐coordinating cysteine residues to oxidation. This picture of probabilistic zinc occupation agrees with a previous structure and energy analysis on zinc finger proteins, and thus it may be more widely applicable to other classes of reactive zinc‐binding proteins. © 2013 Wiley Periodicals, Inc.